2018
DOI: 10.1089/dia.2017.0455
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sampling Duration for Continuous Glucose Monitoring to Determine Long-Term Glycemic Control

Abstract: Fourteen days of CGM data provide a good estimation of glucose metrics for a 3-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(180 citation statements)
references
References 6 publications
8
166
0
6
Order By: Relevance
“…While GMI is generally suggested to be calculated from at least 10 days of sensor use, 27 a recent study indicates that 5 days of sensor data can provide an estimation of mean glucose concentration that is reasonably wellcorrelated with that calculated from a 3-month period of use. 39 The GMI was an average of 6.9%, 7.2%, and 7.5% based on ST data for adults, adolescents, and children, respectively, compared to an average of 6.9%, 6.8%, and 7.0% based on HCL data. While long-term studies are needed, these results, in combination with the decreased percentage of time in hypoglycemia and hyperglycemia and decreased coefficient of variation during HCL compared to ST, are encouraging and indicate that the Omnipod personalized MPC algorithm has the potential to improve overall glycemic control.…”
Section: Discussionmentioning
confidence: 87%
“…While GMI is generally suggested to be calculated from at least 10 days of sensor use, 27 a recent study indicates that 5 days of sensor data can provide an estimation of mean glucose concentration that is reasonably wellcorrelated with that calculated from a 3-month period of use. 39 The GMI was an average of 6.9%, 7.2%, and 7.5% based on ST data for adults, adolescents, and children, respectively, compared to an average of 6.9%, 6.8%, and 7.0% based on HCL data. While long-term studies are needed, these results, in combination with the decreased percentage of time in hypoglycemia and hyperglycemia and decreased coefficient of variation during HCL compared to ST, are encouraging and indicate that the Omnipod personalized MPC algorithm has the potential to improve overall glycemic control.…”
Section: Discussionmentioning
confidence: 87%
“…The comparability of CGM systems and the central laboratory measurements of HbA 1c levels were additional strengths of the present study. The choice to analyse participants with at least 14 days of CGM data was justified by separate studies showing that this amount of data provides a good estimate of glucose metrics for a 3‐month period; however, most participants evaluated in the present study provided more than twice this amount.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Two studies showed that glucose patterns observed during a 14-day period of CGM are already representative of interstitial glucose patterns seen over a longer period of time (3 months). 10,11 Thus, short-term CGM use is relevant to uncover otherwise missed glycaemic excursion when assessed via self-monitoring of blood glucose (SMBG) and HbA1c only. Previous measures of diabetes management (HbA1c, glucometer data) are being challenged, as various CGMderived metrics become available (e.g.…”
Section: Introductionmentioning
confidence: 99%